ANALISA KEBUTUHAN MATERIAL DAN RANTAI PADA PROSES PRODUKSI MESIN TEKUK PLAT HIDROLIK - Eka Putra, Ismet; Wardianto, Dedi; Juliantoni, Juliantoni (Jurnal Teknologi dan Vokasi, 2024)
A plate bending machine or what is called a bending machine, is the process of forming sheet metal (plate) so that it conforms to the planned shape and size. This research applies hydraulic technology to the plate forming and bending process. This bending machine applies a clamping mechanism to the plate and applies a load using hydraulic power to bend the plate. In making this bending machine, it is necessary to analyze the material requirements and the production process chain for an effective hydraulic plate bending machine. Making a hydraulic plate bending machine is divided into several steps that must be carried out and prepared first, namely: Identifying work drawings, planning material selection, preparing materials, preparing tools and machines, carrying out work and finishing processes. The materials used to make components of the hydraulic plate bending machine are 0.6 mm thick ST37 plate with components in the form of clamp parts measuring 1400mm X 196mm 250mm x 95mm, Frame part measuring 1000mm x 600mm. The transmission system used is a hydraulic system to push the bending part. Then, to lift the plate clamp part, use the lever system on the left and right of the hydraulic plate bending machine. The machines and equipment used in making hydraulic plate bending machines are measuring equipment, volume reduction equipment, welding equipment, assembly equipment and finishing equipment.